Hepatocellular carcinoma metastasis to the mandible: a challenging diagnosis - Mastrofrancisco, Rosana; Marcucci, Marcelo; Costa, Anderson Costa Lino; Palma, Luiz Felipe (Journal of Oral Diagnosis, 2023)
Introduction: Metastasis of hepatocellular carcinoma (HCC) to the mandible is an extre-mely rare condition with less than a hundred cases reported worldwide. Such lesions do not have any pathognomonic clinical, radiologic, or histologic features, and they can mimic many other conditions or diseases with orofacial involvement. Case report: We present an interesting but intriguing case of metastasis of HCC to the mandible, which presented as an orofacial swelling accompanied by intense pain and spontaneous bleeding following tooth removal. Conclusion: This paper highlights the importance of integration of the in-depth medical history of the patient, clinical findings, and microscopic examinations in cases of uncommon oral lesions of challenging diagnosis.